Analysis of Aroma Compounds in Tofu from Lembang, Sumedang and Garut West Java, Indonesia - Junitasari, Assyifa (Science Education and Application Journal, 2021)
Tofu from Lembang, Tofu from Sumedang and Tofu from Garut are three types tofu that are produced in different places, but still close. Although made from the same raw material that is soy, every tofu will produce a different tofu, both in terms of taste, aroma, texture and suppleness. Differences in the type of flavour compouds used can also be a factor causing divergence of any tofu product. The characteristic of the tofu were determined by identifying the flavour compouds GC-MS, as well as organoleptic tests. To determine differences in compound-producing falvour in the tofu. The results extraction method was carried out on tofu samples using n-pentane as solvent then analyzed using GC-MS. Flavour compounds of all three types of tofu included into the ester group, alkenes and aldehydes. Organoleptic tests show that the panelists prefered. Tofu from Sumedang for test of colour appearance (82%), for the test texture panelists like Tofu from Garut (83%), for test of elasticity panelists prefered Tofu from Garut Lembang (75%), for taste test panelists prefered Tofu from Lembang (88%), panelists prefered Tofu from Lembang for flavour test (82%).